2021
DOI: 10.1038/s41598-021-94528-3
|View full text |Cite
|
Sign up to set email alerts
|

Lowering DNA binding affinity of SssI DNA methyltransferase does not enhance the specificity of targeted DNA methylation in E. coli

Abstract: Targeted DNA methylation is a technique that aims to methylate cytosines in selected genomic loci. In the most widely used approach a CG-specific DNA methyltransferase (MTase) is fused to a sequence specific DNA binding protein, which binds in the vicinity of the targeted CG site(s). Although the technique has high potential for studying the role of DNA methylation in higher eukaryotes, its usefulness is hampered by insufficient methylation specificity. One of the approaches proposed to suppress methylation at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…M.SssI from the Mollicutes spiroplasma species is a bacterial methylase that catalyzes specifically CG methylation [ 40 ]. M.SssI was shown to be active in vitro, associated with Zinc Finger (ZF) proteins [ 4 , 54 ], triple-helix-forming oligonucleotides [ 48 ] or catalytically-inactive Cas9 (dCas9) [ 28 ] and in vivo with dCas9 in E. coli [ 42 , 53 ], mammalian cells [ 52 ], mouse oocytes or embryos [ 55 ] or with Transcription Activator-Like Effector (TALE) fusion proteins in mouse [ 56 ]. The ability of different M.SssI variants fused to a dCas9 to induce methylation in a specific locus was also demonstrated in Arabidopsis [ 13 ], as well as the potential of the newly acquired methylation to be inherited .…”
Section: Introductionmentioning
confidence: 99%
“…M.SssI from the Mollicutes spiroplasma species is a bacterial methylase that catalyzes specifically CG methylation [ 40 ]. M.SssI was shown to be active in vitro, associated with Zinc Finger (ZF) proteins [ 4 , 54 ], triple-helix-forming oligonucleotides [ 48 ] or catalytically-inactive Cas9 (dCas9) [ 28 ] and in vivo with dCas9 in E. coli [ 42 , 53 ], mammalian cells [ 52 ], mouse oocytes or embryos [ 55 ] or with Transcription Activator-Like Effector (TALE) fusion proteins in mouse [ 56 ]. The ability of different M.SssI variants fused to a dCas9 to induce methylation in a specific locus was also demonstrated in Arabidopsis [ 13 ], as well as the potential of the newly acquired methylation to be inherited .…”
Section: Introductionmentioning
confidence: 99%
“…For M.SssI (Q147L), the authors analyzed candidate gRNA off-target sites of the gRNA and reported no off-target methylation-yet, this off-target analysis strategy is insufficient in that it does not assess the aforementioned off-target methylation independent of dCas9 by the methyltransferase domain as has been extensively demonstrated. Though the authors also performed reduced-representation bisulfite sequencing, they correctly conclude that a failure to detect off-target effects with these approaches does not equate to an absence of off-target effects and, indeed, a more recent study presented evidence that the Q147L mutation in M.SssI does not reduce its nonspecific activity [48], instead only reducing its catalytic activity which suggests that in the original study, the Q147L mutation leads to off-target methylation that is below the threshold of detection. Off-target detection is highly dependent on the power and comprehensiveness of the detection method; it is likely that deep whole-genome methylation sequencing-which was not used in either study-would reveal the true extent of off-target methylation of these engineered epigenetic editor variants.…”
Section: Enzymatic Epigenetic Engineering For Targeted Methylation An...mentioning
confidence: 97%
“…To address issues of leaky gene expression, the specificity of zinc finger protein binding and transferase activity can be fine-tuned. For example, when epigenetic modifying proteins are fused with Cas9’s targeting capabilities, they offer novel avenues for precision gene regulation (Figure C).…”
Section: Designing Epigenetic Gene Regulatory Toolsmentioning
confidence: 99%